Using Wattpad Application to Improve the Recount Text Writing Skill of the Tenth Graders of SMA N 3 Temanggung in the School Year of 2018/2019 - Isti Rokha Rukun (Faculty of Education and Teachers Training, 2019)
USING WATTPAD APPLICATION TO IMPROVE THE RECOUNTTEXT WRITING SKILL OF THE TENTH GRADERS OF SMA N 3TEMANGGUNG IN THE SCHOOL YEAR OF 2018/2019 ISTI ROKHAEnglish Department Faculty of Education and Teachers TrainingTidar UniverisityIstiroha72@gmail.comABSTRACT English is one of the international languages. In teaching English, there are four language skills. They are listening, speaking, reading, and writing. Writing is a language skill to express opinions, feelings, and ideas into the arrangement. However, the tenth graders of SMA N 3 Temanggung in the school year of 2018/2019 still got difficulty in writing, especially in writing recount text. The students’ average score is 65, wile the standard minimum score of the learning target is70. It was caused by the students’ low motivation in learning writing and the monotonous media that are used by the teacher. There are two objectives of this research. First, to know whether or not wattpad application motivates the students in learning writing of recount text of the tenth graders of SMA N 3 Temanggung in the school year of 2018/2019. Second, to find out whether or not teaching writing using wattpad application improve the students’ writing skill of recount text of the tenth graders of SMA N 3 Temanggung in the school year of 2018/2019. The writer conducted a classroom action research. The subject of this research is X IPA 3 of SMA N 3 Temanggung in the school year of 2018/2019 involving 15 males and 21 females. This research was divided into Pre-Cycle and two-Cycles, they are: Cycle I and Cycle II. The writer used observation sheet, questionnaire, and documentation to collect the data. In analyzing data, the writer used qualitative and quantitative measurement to find out the result.The writer found that the use of wattpad application as media can increase the students’ learning motivation. The observation and questionnaire results indicate the students’ have better motivation in learning writing of recount text. The observation percentage in Pre-Cycle is 44.16%, in Cycle I 61.38%, is and it becomes 76.38% in Cycle II. The total improvement is 32.22%. In Pre-Cycle test, the average score of writing recount text is 63.27. After the writer using wattpad application as media, the students average score in Cycle I is 66.55 while in Cycle II is 73.36. The improvement from Pre-Cycle to Cycle I test is 3.28 points, and from Cycle I test to Cycle II test is 6.81 points. Overall the total improvement from Pre-Cycle test to Cycle II test is 10.9 points.Based on the above results, the writer concludes that the use of wattpad application as media in writing recount text can improve the students’ learning motivation in writing recount text and the recount text writing skill of the tenth graders of SMA N 3 Temanggung in the school year of 2018/2019.Keywords: Recount Text, Wattpad Application Media, Writing Skill